Emerging challenges in the design of selective substrates, inhibitors and activity‐based probes for indistinguishable proteases. (29th January 2017) - Kasperkiewicz, Paulina; Poreba, Marcin; Groborz, Katarzyna; Drag, Marcin
Abstract : Proteases are enzymes that hydrolyze the peptide bond of peptide substrates and proteins. Despite significant progress in recent years, one of the greatest challenges in the design and testing of substrates, inhibitors and activity‐based probes for proteases is achieving specificity toward only one enzyme. In this review, we describe important concepts in substrate specificity determination techniques used to distinguish individual proteases. Abstract : Proteases are enzymes that hydrolyze the peptide bond of peptide substrates and proteins. Despite significant progress in recent years, one of the greatest challenges in the design and testing of substrates, inhibitors and activity‐based probes for proteolytic enzymes is achieving specificity toward only one enzyme. This specificity is particularly important if the enzyme is present with other enzymes with a similar catalytic mechanism and substrate specificity but completely different functionality. The cross‐reactivity of substrates, inhibitors and activity‐based probes with other enzymes can significantly impair or even prevent investigations of a target protease. In this review, we describe important concepts and the latest challenges, focusing mainly on peptide‐based substrate specificity techniques used to distinguish individual enzymes within major protease families.